2020
DOI: 10.1177/0363546520938771
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Allograft Transplantation After Anterior Cruciate Ligament Reconstruction Can Improve Knee Stability: A Comparison of Medial and Lateral Procedures

Abstract: Background: The purpose of this study was to evaluate the clinical score and stability after meniscal allograft transplantation (MAT) after a previous anterior cruciate ligament (ACL) reconstruction. Hypothesis: Medial MAT would improve anteroposterior stability, and lateral MAT would improve rotational stability. Study Design: Cohort study; Level of evidence, 3. Method: We retrospectively investigated 31 cases of MAT after a previous total or nearly total meniscectomy and ACL reconstruction between November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…15,33 Moreover, no study has analyzed only the outcomes of medial MAT, although factors affecting the outcomes of medial and lateral MAT might be different. 1,12,35 The purpose of this study was to determine the survival rate of the graft after medial MAT and investigate patient factors that affect its survival. We hypothesized that certain patient factors would influence the survival rate of the graft after medial MAT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,33 Moreover, no study has analyzed only the outcomes of medial MAT, although factors affecting the outcomes of medial and lateral MAT might be different. 1,12,35 The purpose of this study was to determine the survival rate of the graft after medial MAT and investigate patient factors that affect its survival. We hypothesized that certain patient factors would influence the survival rate of the graft after medial MAT.…”
mentioning
confidence: 99%
“…21,27 The medial meniscus is a kind of medial pivot between the convex surface of the femur and the concave surface of the tibia and plays an important role as a joint stabilizer, especially against anterior translation of the tibia during a Lachman test in the anterior cruciate ligament (ACL)–deficient knee. 17,20,22,28,35 Therefore, the surgical methods and indications for medial and lateral MAT are different, and it is important to analyze the MAT results of the medial and lateral compartments separately. Despite these differences, previous studies analyzing factors affecting the results of MAT, such as cartilage, alignment, and instability, have not differentiated between medial and lateral MAT.…”
mentioning
confidence: 99%
“… 15 Zaffagnini et al 31 reported that MMAT with concomitant primary or revision ACLR yielded better results than LMAT in knees with ACL injury or failure of ACLR after meniscectomy. MMAT improved rotational stability as well as anterior posterior stability in a retrospective study by Yoon et al 29 investigating 16 cases of MMAT and 15 cases of LMAT with previous ACLR. In a meta-analysis of 24 studies that compared isolated MAT and combined MAT no significant difference was found in Lysholm, Tegner activity, IKDC subjective, or VAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…30 Degenerative lesions mainly occur on the medial side, and the medial meniscus acts as a secondary stabilizer for anterior translation together with the anterior cruciate ligament (ACL). 29 The lateral meniscus covers 84% of the lateral tibial plateau and transmits approximately 70% of the load. 30 Compared with the medial meniscus, the lateral meniscus is more mobile, and acute traumatic lesions predominantly occur there.…”
mentioning
confidence: 99%
“…An imbalance of muscle force between the medial oblique and lateral femoris muscles can lead to and can result in lateral patella tracking and pain during knee flexion-extension. 5 , 6 Transcutaneous electrical muscle stimulation (TEMS) has been used to rehabilitate the lower extremity function after ACL repair/reconstruction. 7 Medium frequency electrical stimulation of the medial femoral muscle should be useful to improve knee function recovery after ACL reconstruction, but no studies have evaluated this approach.…”
Section: Introductionmentioning
confidence: 99%